2015
DOI: 10.1681/asn.2014080840
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative High-Dose Dexamethasone and Severe AKI after Cardiac Surgery

Abstract: Administration of prophylactic glucocorticoids has been suggested as a strategy to reduce postoperative AKI and other adverse events after cardiac surgery requiring cardiopulmonary bypass. In this post hoc analysis of a large placebo-controlled randomized trial of dexamethasone in 4465 adult patients undergoing cardiac surgery, we examined severe AKI, defined as use of RRT, as a primary outcome. Secondary outcomes were doubling of serum creatinine level or AKI-RRT, as well as AKI-RRT or in-hospital mortality (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…Specifically, urgent RRT following cardiac surgery occurs almost exclusively in patients with CKD stages 4 and 5: in a post hoc analysis of a randomized controlled trial of 4465 adult patients who underwent cardiac surgery, we found that AKI requiring RRT occurred in 0 out of 2247 patients with a baseline eGFR>60 mL/min/1.73 m2, 5 out of 1816 patients (0.3%) with CKD stage 3, 11 out of 300 patients (3.7%) with CKD stage 4, and 17 out of 102 patients (16.7%) with CKD stage 5. 34 …”
Section: Selecting End Points For Clinical Trials In Akimentioning
confidence: 99%
“…Specifically, urgent RRT following cardiac surgery occurs almost exclusively in patients with CKD stages 4 and 5: in a post hoc analysis of a randomized controlled trial of 4465 adult patients who underwent cardiac surgery, we found that AKI requiring RRT occurred in 0 out of 2247 patients with a baseline eGFR>60 mL/min/1.73 m2, 5 out of 1816 patients (0.3%) with CKD stage 3, 11 out of 300 patients (3.7%) with CKD stage 4, and 17 out of 102 patients (16.7%) with CKD stage 5. 34 …”
Section: Selecting End Points For Clinical Trials In Akimentioning
confidence: 99%
“…However, analysis of pre-specified secondary outcomes indicated that high-dose dexamethasone was associated with fewer respiratory complications and reduced postoperative length of stay in the hospital. Also, dexamethasone resulted in a reduced incidence of severe acute kidney injury in patients with advanced chronic kidney disease [7].…”
Section: Introductionmentioning
confidence: 97%
“…9 In a post-hoc analysis of the Dexamethasone for Cardiac Surgery Trial, use of intravenous dexamethasone (a corticosteroid) was associated with a significant relative risk (RR) reduction for dialysis use during the hospital stay (although there were few outcome events and all occurred in patients with chronic kidney disease). 5,10 We conducted a prespecified substudy of the Steroids in Cardiac Surgery (SIRS) trial 11 to test the effect of intraoperative RESEARCH Effect of methylprednisolone on acute kidney injury in patients undergoing cardiac surgery with a cardiopulmonary bypass pump: a randomized controlled trial METHODS: We conducted a prespecified substudy of a randomized controlled trial involving patients undergoing cardiac surgery with cardiopulmonary bypass (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014); patients were recruited from 79 centres in 18 countries. Eligibility criter ia included a moderate-to-high risk of perioperative death based on a preoperative score of 6 or greater on the European System for Cardiac Operative Risk Evaluation I.…”
mentioning
confidence: 99%